(untitled) (Journal of Hama University, 2026)
The aim of the research was to study the effect of using magnetically treated water, temporal feed rationing and the interaction between them on the age and weight of birds at sexual maturity in quails, a total of 312 unsexed one-day-old Japanese quail chicks were used in the experiment, The chicks were randomly divided into four treatments, each containing 78 chicks (T1, normal water and free feeding treatment, T2, normal water and feed rationing treatment for 5 hours daily, T3, magnetized water and free feeding treatment, T4, magnetized water and feed rationing treatment for 5 hours),each treatment included three replicates, each containing 26 chicks, with standardized housing, care and feeding conditions for all treatments. The results showed that female and male birds that consumed magnetized water reached sexual maturity at an earlier and significant age (P≤0.05) (32.43, 41.87) days, respectively, and their average live weight at sexual maturity was significantly higher (P≤0.05) at (160.61, 251.78) g, respectively, compared to male and female birds that consumed normal water and which reached sexual maturity at (33.99, 43.39) days, respectively, While the average live weight at sexual maturity was (149.56, 239.56) g, respectively. The results showed a significant delay (P≤0.05) in the age of sexual maturity of female birds that were subjected to feed rationing (42.95) days, and their average live weight at sexual maturity was significantly lower (P≤0.05) (244.11) g compared to female birds that were fed freely and that reached sexual maturity at the age of (42.31) days, while their average live weight at sexual maturity was (247.23) g, and no significant differences (P>0.05) were observed in the age and weight at sexual maturity between male birds in the two treatments. The results indicated a significant superiority (P≤0.05) when interacting with magnetized water and free feeding T3 in reaching sexual maturity early and increasing the average live weight at sexual maturity compared to T1 and T2 treatments.